العقل و العقلاء في القرآن الكريم - دراسة موضوعية - - حريزي, أسماء (University of Eloued جامعة الوادي, 2018)
يتناول هذا البحث موضوع العقل والعقلاء في القرآن الكريم, حيث يتكلم عن العقل في حياة الإنسان وأن يتجنب تدميره أو تغيبه باتباع شهوات نفسه ونزواتها,حيث اشتمل على مدخل فيه مفهوم العقل والعقلاء ومصطلحات مرادفة للفظة العقل في القرآن الكريم, حيث شمل منها الألباب, والقلب, والفؤاد, ...الخ, ثم انطلق بعدها حديثي عن وظيفة العقل في القرآن الكريم.حيث تطرقت إلى الدعوة إلى التفكر و التدبر ثم التذكر . ليكون حديثي عن مجالات إعمال العقل في القرآن الكريم .وقد اشتمل على الحث على إعمال العقل ونماذج تعطيل العقل في القرآن الكريم, ومنزلقات العقل وآفاته, وكيف يكون الإنسان عاقلا ؟ وكذا الفرق بين العاقل والذكي. وقد خلص البحث إلى جملة من النتائج أهمها:  الإقتداء بالعقلاء وقراءة قصصهم تحفز المرء على نهجهم وحسن استعمال عقلهم وذلك لأن الاهتمام البالغ بفهم أمثال القرآن يؤدي إلى منزلة عالية في العلم. In my research, I dealt with of the " mind" and "rationals " in the Holy Quran. I spoke about the use or exploring of mind in human's life through saving or misusing it as following the self – desires …etc. First of all, I started with the definition in " mind" and "rationals " then , I tackled with the vocabularies that are equivalent to the term " mind" as ; "Alabab, heart, ….ect", and it importance in the Holy Quran . And then proceeded after my talk about the function of reason in the Quran. Where I touched on the call to think and to contrive and then to remember. To be a talk about the areas of the work of " mind" in the Quran and has included of the work of " mind" and models of disabling the" mind" in the Quran and slips of the likes and effects, and how to be rational and difference between the wise and intelligence. To sum up , I conclude some findings as : imitation of "rationals " and learning morals by reading their life and following their stories that motivate us to do as they do. That's why , we had better interest roughly with the best understanding of Quran's morals and wiscloms that lead the human being to succeed and reach his/her superiority within science.
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: العقل ، العقلاء، الدعوة الى التفكير، القرآن الكريم; Mind, rational, call to think, Quran